Digital Business Strategy, Corporate Social Responsibility and Government Support Policy on Revenue Performance among Micro, Small and Medium Enterprises - Nur Syafiqah, Tajudin; Wan Khairul Anuar, Wan Abd Manan; Azizan, Azit; Mazita, Mokhtar (Akademia Baru, 2023)
Globalizations have forced MSMEs to re-strategize in order to remain competitive. Thus, this study aims to investigate the effects of digital business strategy, corporate social and responsibility, and government support policy on revenue performance. This research utilizes a quantitative research design through questionnaire surveys to collect data. The population is based on the Entrepreneurs Directory registered with MSMEs Corporation, while using purposive sampling technique. The data collected were then analyzed using SPSS. The findings elucidate that the digital marketing strategy, corporate social responsibility and government support do positively and significantly impact the revenue performance of MSMEs. The findings also revealed government support policy as the most dominant factor towards the revenue performance of MSMEs. Thus, to survive and thrive in a potentially harsh environment, businesses must effectively deploy and combine their physical, human, and organizational assets. These factors will help micro, small and medium enterprises to beat their competitors and acquire a competitive edge.